Voluntary Tax Compliance UMKM Kota Depok - Ai Annisaa Utami; Zahrudin Zahrudin (Sosio e-Kons, 2017)
ABSTRACT Micro, small, and medium enterprises (SMEs) is an economic sector that has a significant role in national economies. Based on data from the Gross Domestic Product (GDP) in 2011, SMEs have accounted for approximately 57% of total GDP. However, when compared with the contribution of SMEs to tax revenues, there is a miss-match in which the contribution of SMEs on the tax revenue is very small, ie less than 0.5% of total tax revenue .. The study aims to reveal the tax voluntary complaints made by the SMEs in the City Depok, methods of research using a survey of a number of SMEs contained in Depok. The sampling technique used in this research is purposive sampling with a sample of 30 SMEs to Bekasi and Depok. Outcomes of this research is a campaign booklet containing implementation guidelines and technical instructions complain voluntary tax that could be used by the SMEs in Depok City, and other outcomes are scientific publications National levelKeywords: SMEs, Voluntary Tax Compliance, Regulation 46 Year 2013         ABSTRAKUsaha mikro, kecil, dan menengah (UMKM) adalah merupakan sektor ekonomi yang mempunyai peran cukup besar dalam perekenomian nasional. Berdasarkan data Produksi Domestik Bruto (PDB) tahun 2011, UMKM mempunyai kontribusi kurang lebih 57% total PDB. Namun demikian apabila dibandingkan dengan kontribusi UMKM terhadap penerimaan pajak, terdapat miss-match dimana kontribusi UMKM pada penerimaan perpajakan sangat kecil, yaitu kurang lebih 0.5% dari total penerimaan pajak.. Penelitian bertujuan untuk mengungkap voluntary tax complain yang dilakukan oleh para pelaku UMKM di Kota Depok, metode penelitian menggunakan survey terhadap sejumlah UMKM yang terdapat di Kota Depok. Teknik sampling yang digunakan dalam penelitian ini adalah purposive sampling dengan jumlah sampel 30 UMKM untuk wilayah Bekasi dan Depok. Hasil luaran penelitian ini adalah booklet kampanye yang berisi petunjuk pelaksanaan dan petunjuk teknis voluntary tax complain yang bisa digunakan oleh para pelaku UMKM di Kota Depok, dan luaran lainnya adalah publikasi ilmiah tingkat NasionalKata Kunci : UMKM, Voluntary Tax Compliance, PP 46 Tahun 2013